CYSTICERCOSIS AND STERNOCLEIDOMASTOID MUSCLE: A CASE REPORT. (Student's Journal of Health Research Africa, 2023)
Background:Cysticercosis is a parasitic infection caused by the larval form of the tapeworm Taenia solium, typically characterized by cystic formations within various human tissues, most commonly found in the brain and orbit. However, cysticercosis occurring in the craniofacial region, aside from the cerebral and orbital regions, is considered atypical.Case Presentation:In this report, we present an unusual case of a patient who presented with lateral neck swelling. Upon thorough evaluation, the patient was diagnosed with solitary cysticercosis of the sternocleidomastoid muscle (SCM). This case is exceptional due to its infrequency and highlights the importance of considering parasitic infections in the assessment of neck swelling cases. Effective management of this medical condition is achievable through medical interventions. High-resolution sonography has proven to be a reliable diagnostic tool and is valuable for ongoing surveillance.Conclusion:This case report emphasizes the significance of timely identification and proper treatment of cysticercosis, even in atypical anatomical sites such as the SCM.
Keywords: Tapeworm; Cysticercosis cellulosae; Sternocleidomastoid